Decrease in the glyceraldehyde derived advanced glycation end products in the sera of patients with Vogt-Koyanagi-Harada disease. Issue 11 (18th October 2005) - Kitamura, M; Kitaichi, N; Takeuchi, M; Kitamei, H; Namba, K; Yamagishi, S-i; Iwabuchi, K; Onoé, K; Ohno, S
Abstract : Background/aims: Advanced glycation end products (AGEs) are considered to act as mediators of both age related pathologies and diabetic complications. It was recently reported that glyceraldehyde derived AGE (AGE-2) has a strong biological effect on various diseases. The aim of this study was to investigate the serum AGE-2 levels in Vogt-Koyanagi-Harada (VKH) disease. Methods: Sera were obtained from 31 patients with active VKH. 20 of these 31 patients were treated with systemic corticosteroids. As controls, 33 healthy volunteers were also examined. The serum AGE-2 levels were determined with a competitive enzyme linked immunosorbent assay using AGE-2 polyclonal antibody. Results: The mean AGE-2 level in the sera of patients with VKH disease was 4.91 (SD 2.23) U/ml, which was significantly lower than that of the healthy control subjects (8.32 (2.94), p<0.001). The average serum AGE-2 level significantly increased to 13.49 (2.17) U/ml after the patients were treated with systemic corticosteroids (p<0.001). Conclusions: These results suggest that AGE-2 may be involved in the onset of VKH disease.